Longitudinal analysis of 2293 NSCLC patients: A comprehensive study from the TYROL registry. Issue 2 (February 2015) - Kocher, Florian; Hilbe, Wolfgang; Seeber, Andreas; Pircher, Andreas; Schmid, Thomas; Greil, Richard; Auberger, Jutta; Nevinny-Stickel, Meinhard; Sterlacci, William; Tzankov, Alexandar; Jamnig, Herbert; Kohler, Karin; et al.
Highlights: Cumulative analysis of a large NSCLC cohort. Detailed information on symptoms and comorbidities at diagnosis. Correlation of baseline characteristics and outcome. Step-by-step analysis of response and outcome in different therapeutic settings. Abstract: Introduction: The aim of this study was to describe a large consecutive cohort of non-small cell lung cancer (NSCLC) patients treated in daily routine within the last 25 years. An extensive list of general baseline characteristics (comorbidities, laboratory values, symptoms, performance state), NSCLC related factors (stage, histology), treatment related parameters (approach, applied therapies) and outcome (PFS, RFS, OS, perspective of decades) were analyzed in detail. Patients and methods: Medical files of 2293 consecutive NSCLC patients diagnosed between 1989 and 2009 at the Medical University of Innsbruck and affiliated hospitals were retrospectively analyzed. Patients were documented within our institution's comprehensive lung cancer project "Twenty-Year Retrospective of Lung Cancer (TYROL study)". Results: Mean age at diagnosis was 64.1 years and 1611 patients (70.3%) were male. Most patients were diagnosed in stage IV (37.9%). The most frequent comorbidities present at diagnosis were cardiovascular disease (62.1%) and COPD (62.0%). The most common symptoms at diagnosis were coughing (54.7%) and dyspnea (45.3%). Of all 2293 patients 1981 (86.4%) received adequate antineoplastic treatment. In total 874 patients were radically operated, 119 received radiotherapy/radio-chemotherapy and the majority of patients ( n = 1278) were treated in palliative intent. A 2nd, 3rd, 4th and 5th-line palliative therapy was administered to 612, 278, 102, and 36 patients. Median OS, RFS and PFS were 16.4 months, 86.4 months and 5.1 months, respectively. A multitude of factors was associated with all three outcome variables. Of note, outcome has improved stepwise in the recent decade based on increased response rates leading to prolonged OS. Conclusion: This work incorporates most clinical aspects relevant in the treatment of NSCLC and beyond. Therefore, this comprehensive analysis provides a definite benchmark for prognostication and epidemiology of NSCLC in a Western European society.